Enhancing Climate Change Adaptation and Resilience through South-South Technological Innovation - African Climate Policy Centre; Accelerating Impacts of CGIAR Climate Research for Africa; World Meteorological Organization (2025)
This session convened multi-stakeholder participants — UN agencies, regional actors, national research institutions, private sector actors, youth and disability representatives — to explore pathways for accelerating climate-resilient technologies in Africa through South-South cooperation. Key takeaways included • South-South cooperation can accelerate cross-country technology transfer, enabling solutions developed in one country to benefit others, as exemplified by the IPRA project. • Africa must move from aid dependency to African-led investment partnerships, while strengthening self-reliance and regional collaboration. • Technologies must be demand-driven, ensuring smallholder farmers see clear benefits, with actionable solutions linked to local contexts. • Collaboration with national research institutes and centers is critical to co-develop and localize technologies. • Youth engagement, AI, and big data can operationalize anticipatory action when linked to innovation hubs, hackathons, and structured internships. • Inclusive adaptation is essential: co-design with women, youth, persons with disabilities, and pastoralists ensures equitable access and adoption. • Sustainable human capacity requires retention strategies, career pathways, and local innovation centers to prevent brain drain. • Innovative financing, including blended finance and value-chain approaches, can catalyze private investment, ensure inclusion, and create sustainable markets.